Impact of genomics on the surgical management of melanoma. Issue 2 (17th January 2018) - Ferguson, P. M.; Long, G. V.; Scolyer, R. A.; Thompson, J. F.
Abstract : Background: Although surgery for early‐stage melanoma offers the best chance of cure, recent advances in molecular medicine have revolutionized the management of late‐stage melanoma, leading to significant improvements in clinical outcomes. Research into the genomic drivers of disease and cancer immunology has not only ushered in a new era of targeted and immune‐based therapies for patients with metastatic melanoma, but has also provided new tools for monitoring disease recurrence and selecting therapeutic strategies. These advances present new opportunities and challenges to the surgeon treating patients with melanoma. Methods: The literature was reviewed to evaluate diagnostic and therapeutic advances in the management of cutaneous melanoma, and to highlight the impact of these advances on surgical decision‐making. Results: Genomic testing is not required in the surgical management of primary melanoma, although it can provide useful information in some situations. Circulating nucleic acids from melanoma cells can be detected in peripheral blood to predict disease recurrence before it manifests clinically, but validation is required before routine clinical application. BRAF mutation testing is the standard of care for all patients with advanced disease to guide therapy, including the planning of surgery in adjuvant and neoadjuvant settings. Conclusion: Surgery remains central for managing primary melanoma, and is an important element of integrated multidisciplinary care in advanced disease, particularly for patients with resectable metastases. The field will undergo further change as clinical trials address the relationships between surgery, radiotherapy and systemic therapy for patients with high‐risk, early‐stage and advanced melanoma. Abstract : Great advances